Gagasan Periodisasi Masa Jabatan Anggota Dewan Perwakilan Rakyat Dan Dewan Perwakilan Daerah Dalam Perspektif Demokrasi Konstitusional - Tsabbit Aqdamana (Universitas Islam Indonesia, 2022)
There are no rules for the periodization of the terms of office for House of Representatives (DPR) and Regional Representatives Council (DPD) members both in the constitution and relevant laws which leads to the vacuum of law, the issue of the absence of periodization of terms of office for the DPR and DPD is crucial as seen from the history of authoritarianism during the New Order period, there was an abuse of power. In many cases, people who have been in power for a long time often abuse their power. The formulation of the problems in this study are: first, what is the urgency of the periodization of the term of office of members of the DPR and DPRD of the Republic of Indonesia in the perspective of constitutional democracy? Second, how is the idea of a periodization of the term of office of the members of the DPR and the DPD of the Republic of Indonesia in the perspective of constitutional democracy? This study uses normative legal research methods and uses two approaches, namely statutory and conceptual approaches, the data sources used are primary legal materials in the form of laws and regulations, secondary legal materials in the form of literature, books and journal articles, legal materials are analyzed descriptively qualitatively. The results of this study conclude, the idea of periodizing the term of office of DPR and DPD members based on a constitutional democracy perspective, requires revision of the addition of paragraphs to Articles 76 and 252 of the MD3 Law, relating to the affirmation of how many years in office are considered one period, both in the DPR and DPD and also need to be revised Article 76 paragraph (4), and Article 252 paragraph (5) of the MD3 Law, relates to the idea of periodizing the term of office for only two terms and the most relevant institution is given the authority to assess whether candidates for council members have had two terms or not, the General Election Commission (KPU).Key Words: Periodization of tenure; DPR and DPD members; constitutional democracy AbstrakTidak adanya aturan periodisasi masa jabatan anggota DPR dan DPD baik di konstitusi maupun undang-undang sehingga terjadilah kekosongan hukum, persoalan mengenai tidak adanya periodisasi masa jabatan bagi DPR dan DPD menjadi penting karena dilihat dari sejarah otoritarianisme masa orde baru terjadi penyalahgunaan kekuasaan. Dalam banyak kasus orang berkuasa yang lama justru sering menyalahgunakan kekuasaannya. Rumusan masalah dalam penelitian ini adalah: pertama, apa urgensi periodisasi masa jabatan anggota Dewan Perwakilan Rakyat dan Dewan Perwakilan Daerah Republik Indonesia dalam perspektif demokrasi konstitusioal? Kedua, bagaimana gagasan periodisasi masa jabatan anggota Dewan Perwakilan Rakyat dan Dewan Perwakilan Daerah Republik Indonesia dalam perspektif demokrasi konstitusioal? Penelitian ini menggunakan metode penelitian hukum normatif dan menggunakan dua pendekatan yaitu pendekatan undang-undang dan konseptual, sumber data yang digunakan adalah bahan hukum primer berupa peraturan perundang-undangan, bahan hukum sekunder berupa literatur, buku dan jurnal, bahan hukum dianalisis secara deskriptif kualitatif. Hasil penelitian ini menyimpulkan, gagasan periodisasi masa jabatan anggota DPR dan DPD berdasarkan perspektif demokrasi konstitusional, maka diperlukan revisi penambahan ayat pada Pasal 76 dan 252 UU MD3, berkaitan tentang penegasan berapa tahun menjabat dianggap satu periode, baik di DPR dan DPD serta perlu direvisi juga Pasal 76 ayat (4), dan Pasal 252 ayat (5) UU MD3, berkaitan tentang gagasan periodisasi masa jabatan hanya dua periode serta lembaga yang paling relevan diberikan kewenangan untuk menilai apakah calon anggota dewan sudah dua periode apakah belum adalah Komisi Pemilahan Umum (KPU).Kata-kata Kunci: Periodisasi masa jabatan; anggota DPR dan DPD; demokrasi konstitusional